UPAYA PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL DISCOVERY LEARNING DI SEKOLAH DASAR - Ririn Andriani Kumala Dewi; Liyana Sunanto; Casniti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low activeness and student learning outcomes in IPAS subjects. From the results of observations, it is known that there are still many activeness scores and student learning outcomes that are still below the minimum completeness criteria (KKM), so it is necessary to take action to improve student activeness and learning outcomes. The purpose of this study was to determine the application of the discovery learning model, student activeness, and student learning outcomes in IPAS subjects with the research subject of 24 class IV students of UPTD SDN 1 Tegalgirang, Bangodua District, Indramayu Regency. This research uses the PTK method with the discovery learning learning model. The data collection techniques used were test sheets and observation sheets. Based on the results of the research in cycle I, the application of the discovery learning model obtained a score of 50%, increased by 64% in cycle II, increased to 87% in cycle III. Student activeness in cycle I obtained a value of 43% increased by 61% in cycle II increased to 86% in cycle III. Student learning outcomes in cycle I obtained a score of 33.3% increased to 58.3% in cycle II increased to 87% in cycle III.